First record of the genus Hephathus Ribaut (Hemiptera: Cicadellidae: Macropsinae) from China - Yang, Liyuan; Zhang, Yalin (Zootaxa, 2015)
The genus Hephathus with its species Hephathus freyi (Fieber, 1868) is recorded for the first time from China. A new species Hephathus dilatatus is described and illustrated. An updated species checklist with distribution of the genus Hephathus is also provided.